Comparison between pre-hospital and in-hospital ST-Elevation Myocardial Infarction (STEMI) from 2003 to 2016 in New South Wales, Australia: a population-linkage data analysis. (14th October 2021) - Ratwatte, S; Ng, A; Hyun, K; Weber, C; Boroumand, F; Kritharides, L; Brieger, D
Abstract: Background: Outcomes among patients presenting to hospital with STEMI (PH-STEMI) are favourably impacted by access to reperfusion, which has improved in Australia in recent years. Reperfusion rates and outcomes among patients with in-hospital STEMI (IH-STEMI) in Australia are not well described. Purpose: We compared frequency of percutaneous coronary intervention (PCI) and all-cause mortality trends between patients with PH-STEMI and IH-STEMI over 13-years in a statewide cohort. Methods: Patients diagnosed with STEMI (both PH and IH) were identified from the NSW Admitted-Patient-Data-Collection registry from 2003 to 2016 and linked to the death registry until 31-December-2018. We calculated the proportion with PCI over time, and rate of long-term mortality was determined with adjustment for age, sex, year of presentation and PCI. Results: 66, 794 STEMI patients were identified; 57, 721 (86%) had PH-STEMI. Patients with IH-STEMI were older (mean±SD: 75±13 vs 66±14 years), and more likely to be female (46.2% vs 29.8%) than PH-STEMIs. Patients with IH-STEMI were less likely to undergo PCI (17.1% vs 55.8%). From 2003-4 to 2015-6, overall rate of PCI increased for STEMI, but remained lower for IH-STEMI compared to PH-STEMI (9.5% to 23.9% vs 40.4% to 65.5% respectively). All-cause mortality from STEMI fell over time in both groups. Predictors of mortality improvement in the PH and IH-STEMI populations respectively included PCI: (adjusted hazard ratio [aHR]=0.48, 95% confidence interval [CI]: 0.46–0.49 and (aHR=0.48 [95% CI: 0.44–0.53) and year of event: (aHR=0.74 [95% CI: 0.69–0.8] and aHR=0.79 [95% CI: 0.70–0.88]). Adding the interaction term PCI by year group to the mortality models showed that this progressive reduction in mortality by year grouping was accounted for by the performance of PCI in the PH-STEMI group (p<0.0001) but not in the IH-STEMI group (p=0.65). Conclusion: A fall in mortality in patients with PH-STEMI in NSW was observed from 2003 to 2016 and was accounted for by increasing use of PCI. A more modest fall in mortality was seen in patients with IH-STEMI and this was independent of PCI which was under utilised in this population. Efforts to further improve outcomes in STEMI should include a greater focus on patients with in-hospital events. FUNDunding Acknowledgement: Type of funding sources: None.